2022
DOI: 10.3389/fphar.2022.1019411
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic analysis, renal safety, and dosing optimization of polymyxin B in lung transplant recipients with pneumonia: A prospective study

Abstract: Objectives: This study aims to characterize the population pharmacokinetics of polymyxin B in lung transplant recipients and optimize its dosage regimens.Patients and methods: This prospective study involved carbapenem-resistant organisms-infected patients treated with polymyxin B. The population pharmacokinetic model was developed using the NONMEM program. The clinical outcomes including clinical treatment efficacy, microbiological efficacy, nephrotoxicity, and hyperpigmentation were assessed. Monte Carlo sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…One reason for this difference may be that the proportion of patients with renal dysfunction in the present study population reached 68.1%, which was similar to that of the study population of Yu et al and Li et al, whose models were developed based on patients with renal transplant and various renal functions 22,23 . Notably, in addition to the PMB PopPK model developed in our study, several other one‐compartment models that concluded that CrCL is a significant covariate have been developed in Asian populations 22,23,38 . Currently, the effect of ethnicity on PMB pharmacokinetics remains unclear.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…One reason for this difference may be that the proportion of patients with renal dysfunction in the present study population reached 68.1%, which was similar to that of the study population of Yu et al and Li et al, whose models were developed based on patients with renal transplant and various renal functions 22,23 . Notably, in addition to the PMB PopPK model developed in our study, several other one‐compartment models that concluded that CrCL is a significant covariate have been developed in Asian populations 22,23,38 . Currently, the effect of ethnicity on PMB pharmacokinetics remains unclear.…”
Section: Discussionsupporting
confidence: 66%
“…22,23 Notably, in addition to the PMB PopPK model developed in our study, several other one-compartment models that concluded that CrCL is a significant covariate have been developed in Asian populations. 22,23,38 Currently, the effect of ethnicity on PMB pharmacokinetics remains unclear. Given the conflicting findings of the existing studies, larger prospective and international multi-centre studies are needed to validate the roles of renal function and ethnicity in PMB clearance.…”
Section: Discussionmentioning
confidence: 99%